Maladaptive Plasticity in Levodopa-Induced Dyskinesias and Tardive Dyskinesias: Old and New Insights on the Effects of Dopamine Receptor Pharmacology - Cerasa, Antonio; Fasano, Alfonso; Morgante, Francesca; Koch, Giacomo; Quattrone, Aldo (Frontiers in Neurology, 2014)
Maladaptive plasticity can be defined as behavioral loss or even development of disease symptoms resulting from aberrant plasticity changes in the human brain. Hyperkinetic movement disorders, either in the neurological or psychiatric realms, have been associated with maladaptive neural plasticity that can be expressed by functional changes such as an increase in transmitter release, receptor regulation and synaptic plasticity or anatomical modifications such as axonal regeneration, sprouting, synaptogenesis and neurogenesis. Recent evidence from human and animal models provided support to the hypothesis that these phenomena likely depend upon altered dopamine turnover induced by long-term drug treatment. However, it is still unclear how and where these altered mechanisms of cortical plasticity may be localized. The current article will provide an up-to-date overview of these issues together with some reflections on future studies in the field, particularly focusing on two specific disorders (levodopa-induced dyskinesias in Parkinson’s disease patients and tardive dyskinesias in schizophrenic patients) where the modern neuroimaging approaches have recently provided new fundamental insights.